THE EFFECT OF JOURNAL WRITING TECHNIQUE ON STUDENTS’ WRITING ABILITY - Eliwarti Eliwarti; Indah Tri Purwanti (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2021)
This quasi experimental research aims at looking at the effect of Journal Writing technique on students’ ability in writing a paragraph. Specifically, the research answers the research questions about the students’ ability in writing, the effect of Journal Writing technique on the students’ ability in writing, and the students’ attitude toward Journal Writing technique applied in their Writing class. The sample are one class from the second semester of English Department students in 2017-2018 academic year. The data were collected through writing test and the distribution of a set of questionnaire. The results show that nearly 60% of students’ ability ini writing is at Average to Good level before the treatment. After the treatment, 56.76% of their ability is at Good to Excellent level. To test whether the increased score is statistically significant or not, the data were analyzed using t-test. Having t-obs (8.26) which is higher than t-table (2.030), it can be said that the teaching of writing using Journal Writing technique significantly effects the students’ ability in writing paragraph. The data from questionnaire support the previous findings where nearly 64% students have ‘high’ attitude toward Journal Writing technique applied in their class.